Menu satisfaction level at the university student cafeteria / Norlaila Abdullah …[et al.] - Abdullah, Norlaila; Jamaluddin, Sabariah; Mustafa, Lily Mazlifa; Husin, Zuhariah; Yusop, Yuzainizam; Abul Hasan Ashari, Anis; Md Thani, Azlan; Md Pauzi, Suria Fadhillah; Abu Bakar, Rosliza; Ahmad Azam, Faizah Azam; Ku Muhamad, Ku Intan Safinas (2009)
This study examines and investigates the level of menu satisfaction at the student cafeteria in line with one of the provisions in the clients' charter of providing efficient and effective services through continuous improvement (UiTM quality policy). Records indicate that 118 (69.4%) of complaints by students are on dissatisfaction on food served. Corresponding students' survey findings indicate that 78% are dissatisfied with the monotonous daily menu at the cafeteria. Cafeteria in-house investigations reveal the existence of food management and purchasing mismatch. A creative approach, a Student Based Menu Plan (SBMP) for a month on rolling procedure basis, has been recommended and implemented and given recognition by the Dietician officer at the Hospital Tengku Ampuan Afzan in Kuantan. Latest survey on students' satisfaction indicates 51.2% satisfaction level or 129% improvements. Although the SBMP was not able to achieve the project's main objective of attaining a 75% level of menu satisfaction, as the stretch target, this study has accomplished drastic positive change among the students' perspectives of the university cafeterias.